2018
DOI: 10.3389/fvets.2018.00098
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Findings in 41 Dogs Treated with Bone Marrow Aspirate Concentrate and Platelet-Rich Plasma for a Supraspinatus Tendinopathy: A Retrospective Study

Abstract: Objective To report sonographic findings for dogs with a supraspinatus tendinopathy (ST) treated with an ultrasound-guided intratendinous injection of bone marrow aspirate concentrate (BMAC) and platelet-rich plasma (PRP).Methods Medical records for dogs diagnosed with an ST and treated with a BMAC-PRP injection were reviewed. Data collected included patient signalment, radiographic findings at the time of initial evaluation, and sonographic findings, including cross-sectional area (CSA), fiber pattern, and ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
4
19
0
1
Order By: Relevance
“…Growth factors regulate and stimulate cellular processes during healing. Furthermore, the fibrin clot of PRP provides a matrix for the migration of cells responsible for healing (14,25). Our results are also consistent with findings obtained in previous studies reported that the using of PRP alone or combined with other types of the graft can shorten the required time for tendon healing (6,14).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Growth factors regulate and stimulate cellular processes during healing. Furthermore, the fibrin clot of PRP provides a matrix for the migration of cells responsible for healing (14,25). Our results are also consistent with findings obtained in previous studies reported that the using of PRP alone or combined with other types of the graft can shorten the required time for tendon healing (6,14).…”
Section: Discussionsupporting
confidence: 92%
“…One of the most important clinically relevant findings was that animals treated with PRP, or PRP and vein, accomplished a faster healing and adequate tendon tissue regeneration than those in other groups. This finding might indicate that PRP has the effectiveness to accelerate tendon healing where its efficacy could be attributed to the local delivery of a wide range of growth factors and proteins (14). This finding broadly supports the work of other studies stated that using platelet-rich plasma is essential in the process of tendon healing and accordingly restoring its function.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations